Differences in formant-defined vowel space between native speakers of English and Croatian students of English - Horga, Damir (Array, 1997)
Foreign language learning, as indeed any learning, is a transformation process from an initial state toward a new, target state. Essential components of the languae student s initial state include age, cognitive, connative and motivation aspects, and command of their own native language. The maximum desired, target state is to achieve competence in the foreign language comparable to that of native s! peakers. In the learning process the student approaches the desired state in stages. He/she does not necessarily master all language skills equally well or equally quickly. It is assumed that at the phonetic level the desired state is reached during the early stages of language learning. The research raises the question of the extent to which university students of English master the English vowel system, in production of the ten monophtongal vowels that constitute it. The study also addressed differences between first and fourth-year students. Two groups of subjects (10 freshmen and 10 seniors), native speakers of Croatian took part in the study. Their pronunciation of isolated words containing the ten vowels was subjected to computer analysis, determining the first two formant frequencies. The two-dimensional spaces obtained for the two groups were compared with the formant-defined vowel space of native speakers of English.